Converting colour to length based on the coffee-ring effect for quantitative immunoassays using a ruler as readout. Issue 2 (13th December 2017) - Zhang, Dagan; Gao, Bingbing; Chen, Yangtian; Liu, Hong
Abstract : We report a method for converting the colorimetric results of an enzyme-linked immunosorbent assay (ELISA) into length based on the coffee-ring effect, so that the quantitative detection of analytes can be carried out simply using a ruler. Abstract : We report a method for converting the colorimetric results of an enzyme-linked immunosorbent assay (ELISA) into length based on the coffee-ring effect, so that the quantitative detection of analytes can be carried out simply using a ruler. The influence of the shape and lamination of the paper strip on the test results is studied. As a demonstration, human IgG is quantitatively analyzed. It is found that the width of the colored stains correlates with the concentration of the analyte which can be measured for quantitative analysis. The method is promising for quantitative point-of-care detection of biomarkers under resource-limited settings.